2018
DOI: 10.1016/j.ram.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Validación de una técnica de Dot blot para la detección de Cercospora kikuchii en plantas de soja

Abstract: Cercospora kikuchii is a common pathogen in soybean plants that causes crop spoilage. Its early and precise identification would prevent the misuse of pesticides and allow the initiation of an appropriate treatment. A quick, economical and easy-to-execute technique is the Dot blot, capable of recognizing the presence of a genus-specific protein called CFP (Cercosporin Facilitator Protein). The objective was to validate this technique to guarantee the reliability of the results. For that purpose, 29 infected so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The polyclonal antibodies should be specific against the antigen for which they were prepared and show selectivity and reproducibility [57,58]. Polyclonal antibodies (pAb), representing a more varied collection of paratopes for the same antigen, provided more probabilities of detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyclonal antibodies should be specific against the antigen for which they were prepared and show selectivity and reproducibility [57,58]. Polyclonal antibodies (pAb), representing a more varied collection of paratopes for the same antigen, provided more probabilities of detection.…”
Section: Discussionmentioning
confidence: 99%
“…An important validation when working with pAbs is cross-reactivity [57,58]. It was found that the anti-LvLIP antibodies did not show cross-reactivity and no detection was shown in the TBS controls.…”
Section: Discussionmentioning
confidence: 99%